The restaurant survival strategy in Dairi during the covid 19 pandemic - Sri Rosliana Lubis (Politeknik Pariwisata Medan, 2021)
This study aims to identify and analyze the strategies used by restaurants in Dairi to save their restaurant business in order to survive during Covid 19 which has hit for more than a year. The impact of Covid 19 has been felt by all culinary and tourism businesses. Some of the strategies that were carried out were laying off employees temporarily without a clear limit on when they were rehired. Second, limit the use of restaurant facilities to suppress ordinary operations. Third, the efficiency of restaurant spending. Fourth, selling food online to old acquaintances and customers. Fifth, do it with the